The Phenomenology of Problem Solving. - Yoshimi, Jeffrey (Grazer Philosophische Studien, 2017)
The author outlines a provisional phenomenology of problem solving. He begins by reviewing the history of problem-solving psychology, focusing on the Gestalt approach, which emphasizes the influence of prior knowledge and the occurrence of sudden insights. He then describes problem solving as a process unfolding in a field of consciousness against a background of unconscious knowledge, which encodes action patterns, schemata, and affordances. A global feeling of wrongness or tension is resolved by a series of field transitions, which are guided by peripheral experiences of coherence or "rightness." The author treats the distinction between reproductive thought (in which we rely on existing strategies to solve a problem) and productive thought (in which we struggle to identify new strategies) as a difference in field structure. With reproductive thoughts and actions we perform operations to solve a problem in a semi-automatic sequence. In productive thought, by contrast, a kind of parallel search occurs. This may explain the otherwise obscure phenomenology of struggling to break an impasse.